Intravenous administration of diazepam in patients with chronic liver disease. Issue 12 (December 1976) - Branch, R A; Morgan, M H; James, J; Read, A E
Abstract : The EEG response and drug kinetics after intravenous infusion of diazepam at 1-0 mg/min until nystagmus, dysarthria, and moderate sedation developed, has been investigated in five normal subjects and 17 patients with chronic liver disease. Diazepam induced adequate premedication with a similar clinical response in all subjects with no adverse reactions. Maximal response was during or within five minutes of infusion. The dose of diazepam required in liver chronic disease was 17-9 +/- 1-4 mg (M +/- SEM) compared with 27 +/- 5-4 mg in controls (p less than 0-01). Dose correlated significantly with serum albumin (p less than 0-05). Baseline mean dominant frequency (MDF) and slow wave index (SWI) significantly correlated with albumin (p less than 0-01). After diazepam, the MDF decreased and SWI increased. The change was greatest at the time of maximal clinical response. It was greater in liverdisease and was greatest in patients with previous hepaticencephalopathy. In spite of reduced dose requirements in liver disease, there was no significant difference in plasma concentration at the end of drug infusion...